Climate Resilient Agriculture in Nepal: Challenges, Innovations, and the Path Toward Sustainable Food System - Ghimire, Prapti; Pokhrel, Samikshya; Tiwari, Manjita (Journal of Sustainability and Environmental Management, 2025)
Climate change has seriously threatened agriculture in Nepal due to the vulnerable topography and a significant proportion of the population being dependent on agriculture. This review examines the impact of climate change on agriculture in Nepal, which has contributed to food insecurity and socioeconomic challenges. The increase in greenhouse gases leads to climatic variation, including erratic rainfall patterns, temperature fluctuations, and extreme events such as floods and landslides. Such alterations in climate conditions significantly affect agricultural productivity, thereby putting the livelihoods of millions of farmers, who rely on subsistence farming, at risk. The irregular pattern of weather has led to a decrease in yield, increased pest infestations, and soil degradation, all of which complicate food availability, accessibility, and affordability. Climate-resilient agriculture, an approach that mitigates the adverse effects of climate change, helps build resilience in farming through methods such as agroforestry, conservation agriculture, and stress-tolerant crop varieties, which enhance crop viability and help sustain production in a particular environment. CRA also focuses on the role of biotechnological innovations and technologies, such as GIS and ICT tools, in reducing climate risk and supporting sustainable farming practices. Nepal has adopted various climate change policies and adaptation plans to address specific vulnerabilities related to climate actions. However, their execution is obstructed due to various challenges coming from the socio-economic, policy, and institutional levels. High costs, low levels of awareness, and a weak institutional framework significantly restrict the implementation of resilience strategies. The integration of traditional knowledge, the enhancement of renewable energy sources, and the improvement of water management practices can be effective methods for managing climate risks and ensuring food security. Similarly, research on invasive species, biotechnological solutions, and policy development needs to be strengthened in the future to develop resilience to climate change.